Penggunaan Teknologi Permodelan Maklumat Bangunan (BIM) Dalam Fasa Pembinaan Bagi Menambahbaik Proses Pembinaan Di Malaysia - Khairudin, Khairul Ikhmal; YAHYA, MOHD YAMANI (Research in Management of Technology and Business, 2022)
Building Information Modeling (BIM) is a software that may be utilised throughout the lifecycle of a construction project, including the construction phase. The BIM technology is being utilised on the construction site to analyse the clashes, schedule the work, manage the logistics, and conduct site inspections to improve the current performance of the construction process. The employment of conventional methods on the construction site has caused the construction process to be delayed and ineffective. This is due to a lack of knowledge about the component that will be constructed on the construction site. In this regard, this study was carried out to investigate in greater depth the amount of BIM usage in Malaysia. The scope of this study is limited to construction players in Johor who have been involved in projects that have included BIM. Respondents' information was gathered using quantitative approaches, specifically through the dissemination of questionnaire surveys. According to the results, most respondents who provided feedback agreed with the statement of the question that was presented. This demonstrates that they are aware that the usage of BIM is not limited to the design phase but can also be employed throughout the building phase.